The Impact of Fuel Subsidy Removal on Poverty in Nasarawa State - Bemgba , Paul Terlumun; Adadu, Yahaya Abdullahi (Kashere Journal of Politics and International Relations, 2025)
The removal of fuel subsidy in Nigeria in 2023 represents one of the most impactful fiscal reforms in recent national history, with profound implications for household welfare and poverty levels across the country. This study critically investigates the impact of this policy on poverty in Nasarawa State, leveraging primary data obtained from a structured household survey administered across urban and rural areas of the state. The study examines changes in household income, expenditure, access to social services, and livelihood sustainability before and after subsidy removal. Findings reveal that the policy has significantly exacerbated the incidence of poverty in Nasarawa State, with rural dwellers disproportionately affected due to increased transportation costs, food insecurity, and limited access to palliative measures. While the federal government introduced conditional cash transfers and other social intervention programs to cushion the effect of subsidy removal, the study observed that many of these initiatives were poorly targeted or inadequately implemented, thereby limiting their intended impact. Moreover, the structural weaknesses in existing social safety nets failed to provide meaningful protection for the most vulnerable populations. The study situates its analysis within the broader context of Nigeria’s macroeconomic reform agenda and highlights the paradox of policy intentions versus on-ground realities. It also critiques the short- to medium-term implementation strategy of the subsidy removal, arguing that without robust institutional frameworks and inclusive policy design, such reforms risk deepening inequality and social discontent